Pengaruh Layanan Bimbingan Kelompok Terhadap Peningkatan Pemahaman Edukasi Seks - Luthfiah, Siti; Hilaluddin, Muhammad Nur; Olivia, Yunda Meri; Muslimah; Zamakhsyary, Andrian (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
According to Rahman & Fachrudin (2000), sex education is a conscious and systematic process carried out by schools, families and communities to convey information about sexuality which covers areas such as the development of boys and girls, personal abilities, sexual behavior, social behavior, sexual health, the role of family, school, community and government as well as problems and challenges in its development. Education about sex has been considered pornographic taboo and it is inappropriate to talk about it. There are still few people who understand the importance of sex education for teenagers, so it is difficult to provide sex education to students considering that adolescence is a period of puberty which is very vulnerable to getting caught up in promiscuity and a strong desire to try something new. If this continues without efforts to provide broader and deeper education regarding sex education, there is the potential for negative sexual behavior to emerge. This approach uses a type of quantitative research with a survey method, namely collecting data using a list of statements and giving it to respondents to answer. Apart from that, researchers also used interviews and observations to interview and observe the child's behavior